Pendampingan Belajar Membaca Dengan Metode Kata Lembaga Di Tengah Covid-19 - In Ratnasari, Khurin In; Ulum, M Bustanul (AS-SUNNIYYAH, 2021)
The covid-19 pandemic has an impact on the education sector. where the government makes a policy to conduct distance learning. The researcher conducted community service with MI Nurul Huda as a partner in implementing the institutional word method in learning to read. This article aims to describe the institutional word method and student response rates as well as the three aspects that provide assistance. This research is a qualitative research by conducting interviews in data collection and direct observation to find out the problems that occur. The purpose of this study is to increase social care from the parents / guardians of the students themselves, close relatives of students to the surrounding community who have sibling or non-family relationships. Provide motivation to various parties to have attention to the education of students. not only depending on the school or the teacher. especially when the covid-19 pandemic occurred. In this study, the mentoring strategy and the steps in making a briefing program for various parties can run effectively, efficiently and conducively in this study. The method used is to use the word institution method. In conclusion, after this reading learning assistance activity, students who initially had problems with learning have now begun to be resolved. They don't have to go to school to learn to read. Because, there are parents, close relatives and the surrounding community who are able to teach him to read while at home.